Physicochemical properties, total phenolic content and radical scavenging activity of pasteurized lemon grass (Cymbopogon citratus (DC. ex Nees) stapf) beverage - Gonzales, Maria Kristine Tantingco (UP College of Home Economics, 2012)
Excessive oxidative stress and free radicals can cause several health problems. Studies on medicinal plants such as lemon grass have been carried out since researches revealed that the dietary intake of antioxidant-rich foods can prevent incidences of human diseases. Nowadays, herbal drinks are becoming more popular due to the possible beneficial antioxidant compounds they contain. However, there is still a need to determine the effect of various processing techniques on antioxidant compounds of foods. In this study, the effect of pasteurization on the physicochemical properties, total phenolic content and radical scavenging activity of lemon grass beverage was determined. Nine samples of lemon grass beverage with varying boiling time (5, 10 and 15 minutes) and sugar concentration (10, 14 and 18%) were prepared. Consumer acceptance test was conducted by 50 untrained panelists. Analysis of Variance, Duncan Multiple Range Test and regression analysis were used to determine significant differences among the treatments. Prediction models showed that flavor and overall acceptability increased as sugar concentration increased. The effect of pasteurization on the physicochemical properties, total phenolic content and radical scavenging activity of lemon grass beverage boiled for five minutes and sweetened with sugar at 18% w/v was further studied. Microbiological assessment revealed that aerobic plate count was lowered by pasteurization. Physicochemical results showed that pasteurization increased total soluble solids and titratable acidity whereas pH decreased after heat treatment. Pasteurization increased the total phenolic content but decreased the scavenging capacity of the lemon grass beverage. Generally, storage time of two weeks at refrigerated temperature had no effect on the physicochemical properties of the beverage except for scavenging capacity.